Volubility, Consonant Emergence, and Syllabic Structure in Infants and Toddlers Later Diagnosed With Childhood Apraxia of Speech, Speech Sound Disorder, and Typical Development: A Retrospective Video Analysis. - Overby, Megan S.; Caspari, Susan S.; Schreiber, James (Journal of Speech, Language & Hearing Research, 2019)
Purpose: Studies of infants' early vocalizations have proven helpful in describing the developmental characteristics of various communication disorders. However, few studies have addressed the early vocalizations of infants and toddlers who were later diagnosed, as older children, with childhood apraxia of speech (CAS). We refer to these infants and toddlers as LCAS. Extant studies also often lack a comparison group of infants and toddlers who were later diagnosed, as older children, with a speech sound disorder (SSD). We refer to these infants and toddlers as LSSD. We aimed to compare the volubility, consonant emergence, and syllabic structure from birth to age of 2 years, as observed in home videos, among 3 groups of infants and toddlers: LCAS, LSSD, and typically developing (TD). Method: We assessed the speech-language skills of 17 children (3.5-8.8 years old; 7 with CAS, 5 with SSD, and 5 TD) and transcribed home videos (obtained from parents) of these same children from birth to age of 2 years. Early vocalizations were coded as nonresonant or resonant. Nonresonant vocalizations could not be transcribed with the International Phonetic Alphabet. Resonant (speechlike) vocalizations were broadly transcribed, and resonant consonants were categorized by place, manner, and voicing. Results: Effect size comparisons revealed LCAS infants and toddlers were less voluble, used fewer resonant consonants, had a less diverse phonetic repertoire, and acquired resonant consonants later than either the LSSD or TD participants. For LSSD infants and toddlers, means for these dependent variables were lower than the means demonstrated by the TD group, but effect size were not strong due to LSSD variability. Conclusions: Findings imply there might be clinical "red flags" that could assist the identification of infants and toddlers at risk for later diagnosis of CAS. Data did not support red flags for identifying infants and toddlers at risk for later diagnosis of SSD. Because of significant study limitations, results obtained should be considered preliminary.